In situ measurement of dental resin-based composite volumetric shrinkage and temperature effects using in-fibre bragg grating methods. (July 2019) - Romanyk, Dan L.; Yu, Henry; Grotski, Miranda; Seo, Solbee; Addison, Owen; Dennison, Christopher R.
Abstract: Objectives: Resin-based composites (RBCs) are commonly used in dental restorations. It is known that RBCs undergo volumetric shrinkage during photo-polymerization leading to a detrimental increased stress state at the RBC-tooth interface and potentially early restoration failure. The objectives of this in vitro study were: (1) to ascertain whether shrinkage strain could be measured using in-fibre Bragg grating (FBG) technology, without confounding effects of temperature; and (2) to ascertain whether FBGs can detect alteration in shrinkage strain with introduction of a surface condition change at the RBC-cavity analog interface. Methods: Aluminum cavity analogs with simulated cavity dimensions 3.5 mm height x 2 mm width x 8 mm length and 2 mm wall thickness were secured in a 3D printed experimental jig. Two FBGs were used in the RBC space, one that was covered with a polyimide tube and that measured only temperature, and another that was affected by both mechanical strain and temperature. Experiments to determine if the two FBG system could be used to compensate for thermal artefacts were contrived to verify that a tube-covered and bare FBG measure the same temperature effect (n = 5). In situ photo-polymerization experiments, which consisted of using controlled amounts of SureFil SDR Flow + RBC, were performed to study RBC shrinkage behavior. As-machined (n = 10) and micro-etched (n = 11) cavity analogs were used. Significant differences in FBG measurements, which could indicate the ability of FBGs to detect alterations in strain across surface preparations, were determined using one tail t-tests at 95% confidence. Finally, additional temperature experiments were conducted 5 h after initial light exposure using the same light irradiation regiment to investigate temperature effects within a cured RBC system (n = 3). Results: For temperature measurement, the tubing-covered and bare FBGs measured temperature changes with time-lag of 3.7 ± 1.4 s (tubing-covered FBG relative to bare). For measurements in cured RBC, the bare FBG and tubing-covered FBG measured different strains, with the bare FBG measuring larger apparent strains because this FBG is affected by thermal volumetric expansion of the RBC and a temperature increase of the FBG itself. The tubing covered FBG, that is isolated from volumetric expansion effects, measured relatively less. The interpretation of these results is that thermally-compensated strain measures (in-situ) could require simultaneous use of two FBGs (one strain isolated). In situ measurements of the photo-polymerization procedure for as-machined analogs at two time-points, 500 and 1000 s, were determined to be −485.43 ± 131.06 μstrain and −524.96 ± 134.78 μstrain, respectively. For air-abraded surfaces measures were significantly lower at (p < 0.001) −211.36 ± 12.38 μstrain and −228.07 ± 49.08 μstrain, respectively. Conclusions: To measure shrinkage strain and compensate for associated thermal effects from photo-polymerization, systems employing two FBGs, one of them isolated from thermal volumetric expansion, may be required. The presented approach proved capable of detecting significant alteration in strain across two surface preparations.